The Impact of PPARγ Genetic Variants on IBD Susceptibility and IBD Disease Course - Jessica Mwinyi; Christa Grete-Wenger; Jyrki J. Eloranta; Gerd A. Kullak-Ublick (PPAR Research)
PPARγ is a nuclear receptor that regulates numerous pathways including cytokine expression and immune responses and plays an important role in controlling colon inflammation. We aimed at determining the occurring PPARγ SNPs, at predicting the haplotypes, and at determining the frequency outcome in inflammatory bowel disease (IBD) patients in comparison with healthy controls. We determined genetic variants in the coding exons and flanking intronic sequences of the NR1C3 gene in 284 IBD patients and 194 controls and predicted NR1C3 haplotypes via bioinformatic analysis. We investigated whether certain NR1C3 variants are associated with susceptibility to IBD or its disease course. None of the detected 22 NR1C3 variants were associated with IBD. Two variants with allelic frequencies over 1% were included in haplotype/diplotype analyses. None of the NR3C1 haplotypes showed association with IBD development or disease course. We conclude that NR1C3 haplotypes are not related to IBD susceptibility or IBD disease activity.